Analysis of the Use of Different Decoding Schemes in LDPC Coded OFDM Systems over Indoor PLC Channels - Develi, I.; Kabalci, Y. (Elektronika ir Elektrotechnika, 2014)
Power line communication (PLC) method is a developing technology that is intended to provide a communication platform by using conventional power lines. In this study, bit error rate (BER) performances of low-density parity-check (LDPC) coded orthogonal frequency-division multiplexing (OFDM) systems have been examined over indoor PLC channels. Performances of different LDPC decoder schemes such as belief propagation (BP), weighted bit flipping (WBF) and implementation-efficient reliability ratio based weighted bit flipping (IRRWBF) decoders were investigated in the modelled system. Different indoor channel scenarios that were generated by using new and more realistic PLC channel model proposal were also employed to evaluate the BER performance analyses. The performed simulations in the PLC channels showed that the LDPC codes can provide significant improvement with a remarkable encoding complexity when the BP or IRRWBF decoder is utilized on the receiver unit. DOI: http://dx.doi.org/10.5755/j01.eee.20.10.8879